Urological Cancer 2020 - López, José I. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Urological Cancer 2020 collection contains a set of multidisciplinary contributions to the extraordinary heterogeneity of tumor mechanisms, diagnostic approaches, and therapies of the renal, urinary tract, and prostate cancers, with the intention of offering to interested readers a representative snapshot of the status of urological research.